Development of novel water activity instrument for determining habitability in outer space - Desai, Prarthana P. (The University of Edinburgh, 2021)
This work presents a novel compact water activity measuring device, optimised for planetary and space exploration. Water is a key element for life as we know it and therefore for astrobiology. However, measuring the presence and amount of water alone is not sufficient to determine if an environment is chemically suitable to support microbial life. Water Activity is a measure of the chemically available water for microbes to survive in a substance, thereby acting as a far more reliable indicator of habitability. Since water activity is such an important factor for determining habitability of a region, it is an area of growing interest in astrobiology. Planetary missions have yet to include water activity measurement systems despite their significant potential for addressing the question of habitability. This is because the priority for missions until now has been limited to the search for bulk liquid water. With new water reservoirs found within the solar system such as on icy moons like Enceladus and the recently discovered underground lakes on Mars, measuring water activity becomes important. It is measured routinely in the food industry for measuring longevity of food products using instruments that are, by the requirements of our application, bulky, heavy, power hungry and slow. The aim of this project is to develop a novel water activity meter, which is for the first time optimised for planetary exploration, and will be of huge benefit for the entire space science community involved in studying habitability and life-detection, to answer one of the most profound questions of our lifetime — Does life exist elsewhere in the universe? This was achieved by instrument design and verification of its performance in dynamic real-life condition to advance its Technology Readiness Level. The prototypes presented in this work used capacitive sensing technology to measure relative humidity, which is a function of water activity in a closed system. Innovations in design have led to the faster speed of response, which is required to track dynamic changes in outer space. Field-ready prototypes were designed and deployed in the Mars Analogue sites such as the Boulby mine and the Basque lakes, to validate the instrument. These field tests highlighted some design issues in the earlier versions of the prototype such as poor mechanical strength at junctions of the cables and the limitations of the sensors such as an inevitable measurement offset caused by saturation of the sensor membrane. These problems were solved by upgrading the design in later prototype versions and using an integrated heating element to dispel excess moisture from the sensor membrane. The new prototype design, along with electronics and data acquisition subsystems, was easily portable and capable of multiplexed measurements. These features are new to water activity meters and facilitate ease of transportation and use in space industry. This instrument has successfully contributed to on-going scientific research in astrobiology by monitoring the water activity of Basque lakes in collaboration with the ‘Search for Extra-Terrestrial Genomes’ group at MIT and contributed to a NASA led study on the natural salt pools in the Boulby mine to understand habitability of an ecosystem undisturbed since the past 250 million years.
Keywords: water activity; astrobiology